2016
DOI: 10.1161/atvbaha.116.307874
|View full text |Cite
|
Sign up to set email alerts
|

Mice Expressing Low Levels of CalDAG-GEFI Exhibit Markedly Impaired Platelet Activation With Minor Impact on Hemostasis

Abstract: Objective The tight regulation of platelet adhesiveness, mediated by the αIIbβ3 integrin, is critical for hemostasis and prevention of thrombosis. We recently demonstrated that integrin affinity in platelets is controlled by the guanine nucleotide exchange factor, CalDAG-GEFI (CD-GEFI), and its target, RAP1. In this study, we investigated whether low-level expression of CD-GEFI leads to protection from thrombosis without pathological bleeding in mice. Approach and Results Cdg1low mice were generated by knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
2
17
0
1
Order By: Relevance
“…This marked reduction in Arp2/3 expression, however, has only a very mild effect on platelet integrin activation in vitro and hemostatic plug formation in vivo . In contrast, platelet adhesion, hemostasis and thrombosis were significantly impaired in mice with similar reductions in CalDAG-GEFI 37 or Kindlin-3 23 , highly expressed proteins critical to platelet adhesion and thrombus formation. Thus, the Arp2/3 complex does not seem to be a major regulator of hemostatic plug formation at sites of vascular damage.…”
Section: Discussionmentioning
confidence: 93%
“…This marked reduction in Arp2/3 expression, however, has only a very mild effect on platelet integrin activation in vitro and hemostatic plug formation in vivo . In contrast, platelet adhesion, hemostasis and thrombosis were significantly impaired in mice with similar reductions in CalDAG-GEFI 37 or Kindlin-3 23 , highly expressed proteins critical to platelet adhesion and thrombus formation. Thus, the Arp2/3 complex does not seem to be a major regulator of hemostatic plug formation at sites of vascular damage.…”
Section: Discussionmentioning
confidence: 93%
“…The relatively mild bleeding defect in mice and adult human patients expressing CDGI lacking the C1 domain provides a rationale for targeting the C1‐phosphoinositide interaction in the prevention of atherothrombosis. Our studies in mice expressing CDGIΔC1 and mice expressing low levels of CDGI demonstrated strong protection from experimental thrombosis, including models of arterial thrombosis and immune complex‐mediated thrombocytopenia and thrombosis . On a mechanistic level, the protection from arterial thrombosis is most likely explained by a delay and reduction in integrin activation, the key event in platelet aggregation.…”
Section: Discussionmentioning
confidence: 71%
“…Our studies in mice expressing CDGIΔC1 and mice expressing low levels of CDGI demonstrated strong protection from experimental thrombosis, including models of arterial thrombosis and immune complex-mediated thrombocytopenia and thrombosis. 13,70 On a mechanistic level, the protection from arterial thrombosis is most likely explained by a delay and reduction in integrin activation, the key event in platelet aggregation. CDGI plays a critical role in the near-immediate activation of αIIbβ3, 8 with deficiency in the protein leading to markedly delayed platelet aggregation in mice and humans.…”
Section: Our Studies Have Important Clinical Implications Mutations Inmentioning
confidence: 99%
“…2 The importance of CalDAG GEFI in the intact vasculature has also been demonstrated in several mouse models of hemostasis, atherosclerosis, and thrombotic thrombocytopenia. [3][4][5] Even though human CalDAG GEFI is thought to perform the same function as its murine homolog, a glimpse of the physiologic role of CalDAG GEFI in human platelets has only recently been attained. A point mutation in the human RASGRP2 gene was discovered in 2 homozygous patients by wholeexome sequencing by Canault et al 6 These investigators showed that platelets expressing a CalDAG GEFI mutant (G248W) displayed decreased platelet spreading, aggregation, and adhesion under flow conditions without affecting aIIbb3 activation or CalDAG GEFI protein levels.…”
Section: Blood 8 December 2016 X Volume 128 Number 23 2597mentioning
confidence: 99%